Masked hypertension in children and its relationship with target organ damage. Issue 2 (2015) - Conkar, Seçil; Mir, Sevgi; Sözeri, Betül; Yıldız, Ümmügülsüm; Bulut, İpek Kaplan; Bozovalı, Sibel; Yılmaz, Ebru
No abstract available